Analisis Faktor-Faktor yang Mempengaruhi Keberlanjutan Konflik Antara Monjok dan Karang Taliwang: Perbedaan Identitas dan Perbedaan Sektor Ekonomi - Jamalullail, Syarifah Nurhasanah; Hadiati, Ilmiatun; Anggaraksa, Aldis Priya; Fakhrurrahman, Anang; Putri, Anggun Aulia; Hatami, Lalu Ahmad (Department of International Relations, University of Mataram, 2023)
Differences in identity, encompassing culture, language, and ethnicity, can trigger conflicts, as seen between Monjok and Karang Taliwang. Economic inequality generates dissatisfaction and injustice, further exacerbating ongoing conflicts. The researcher employed a qualitative approach with a descriptive method, utilizing two data sources: primary data obtained through direct interviews and secondary data gathered from literature reviews in various sources such as journals, online articles, and scholarly works related to the topic. Based on the research findings, differences in identity and economic inequality emerge as root causes of sustained conflict. Therefore, the researcher employed several approaches, including social conflict theory, social identity theory, and the concept of economic disparity, to explore these issues. The results indicate that comprehensive efforts from various stakeholders, especially policymakers, are needed for reconciliation, including promoting cross-cultural understanding, reducing economic inequality, implementing collaborative economic development programs, and building connections between conflicting groups.